Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1097/mib.0000000000000840
|View full text |Cite
|
Sign up to set email alerts
|

Luminal Extracellular Vesicles (EVs) in Inflammatory Bowel Disease (IBD) Exhibit Proinflammatory Effects on Epithelial Cells and Macrophages

Abstract: Background Extracellular vesicles (EVs) are membrane-enclosed particles released by cells as a means of intercellular communication. They are potential novel biomarkers, as they are readily isolated from body fluids, and their composition reflects disease pathways. Whether these particles are released from sites of intestinal inflammation in Inflammatory Bowel Disease (IBD) has not previously been determined. Methods EVs were isolated by ultracentrifugation of colonic luminal fluid aspirates, and characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
82
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(87 citation statements)
references
References 34 publications
(32 reference statements)
0
82
0
Order By: Relevance
“…Epithelial cells and macrophages could be activated by luminal exosome treatment, leading to increased production of IL-8 and migratory activity when compared with controls. [62] In animal studies, exosomes isolated from DSSinduced acute colitis mice or Crohn's disease related adherentinvasive Escherichia coli (AIEC)-infected intestinal epithelial cells and macrophages could activate naïve macrophages through activation of NF-κB, ERK, p38, and JNK, and result in increased secretion of pro-inflammatory cytokines TNF-α and IL-6. [14,63] In addition to activating immune and inflammatory responses, depending on the state or type of their parental cell, exosomes have also been shown to suppress the same responses.…”
Section: Proteomic Analyses Of Eev Fractions Identified >1700mentioning
confidence: 99%
“…Epithelial cells and macrophages could be activated by luminal exosome treatment, leading to increased production of IL-8 and migratory activity when compared with controls. [62] In animal studies, exosomes isolated from DSSinduced acute colitis mice or Crohn's disease related adherentinvasive Escherichia coli (AIEC)-infected intestinal epithelial cells and macrophages could activate naïve macrophages through activation of NF-κB, ERK, p38, and JNK, and result in increased secretion of pro-inflammatory cytokines TNF-α and IL-6. [14,63] In addition to activating immune and inflammatory responses, depending on the state or type of their parental cell, exosomes have also been shown to suppress the same responses.…”
Section: Proteomic Analyses Of Eev Fractions Identified >1700mentioning
confidence: 99%
“…EVs can be readily isolated from bodily fluids, such as serum, 50 saliva, 51 urine, 52 and in the intestine from luminal aspirates. 53 The number of EVs and their composition can reflect both healthy and pathological states. 54 Specifically, in IBD an increased number of EVs in the serum and the intestinal lumen 53 was correlated with disease severity and were shown to contain immune cell-and IEC-specific markers as well as many inflammatory markers associated with the diseases.…”
Section: The Biogenesis and Composition Of Extracellular Vesicles (Evs)mentioning
confidence: 99%
“…In addition, these MP constitute a mode of communication through which intestinal cells may influence the luminal microbiome. We have recently reported that extracellular vesicles, derived from the colonic luminal fluid of IBD patients, display pro-inflammatory properties as these MP contain high mRNA and protein levels of IL-6, IL-8, IL-10 and TNF-α, and promote macrophage migration (41). We have also shown that CD39 associates with circulating plasma-derived MP and may directly or indirectly confer functional properties on cells.…”
Section: Cd39 and Exosomes In Ibdmentioning
confidence: 99%